Postnatal Development of the Hippocampal Formation: A Stereological Study in Macaque Monkeys - Jabès, Adeline (2011)
We performed a stereological analysis of neuron number, neuronal soma size, and volume of individual regions and layers of the macaque monkey hippocampal formation during early postnatal development. We found a protracted period of neuron addition in the dentate gyrus throughout the first postnatal year and a concomitant late maturation of the granule cell population and individual dentate gyrus layers that extended beyond the first year of life. Although the development of CA3 generally paralleled that of the dentate gyrus, the distal portion of CA3, which receives direct entorhinal cortex projections, matured earlier than the proximal portion of CA3. CA1 matured earlier than the dentate gyrus and CA3. Interestingly, CA1 stratum lacunosum-moleculare, in which direct entorhinal cortex projections terminate, matured earlier than CA1 strata oriens, pyramidale, and radiatum, in which the CA3 pro jections terminate. The subiculum developed earlier than the dentate gyrus, CA3, and CA1, but not CA2. However, similarly to CA1, the molecular layer of the subiculum, in which the entorhinal cortex projections terminate, was overall more mature in the first post-natal year compared with the stratum pyramidale in which most of the CA1 projections terminate. Unlike other hippocampal fields, volumetric measurements suggested regressive events in the structural maturation of presubicular neurons and circuits. Finally, areal and neuron soma size measurements revealed an early maturation of the parasubiculum. We discuss the functional implications of the differential development of distinct hippocampal circuits for the emergence and maturation of different types of “hippocampus-dependent” memory processes, including spatial and episodic memories.